Prehistoric shifts in tropical cyclone season in the South China sea: evidence from daily resolution records of giant clam shells - Nanyu Zhao; Hong Yan; Ge Shi; Fan Luo; Tao Han; Chengcheng Liu; John Dodson (npj Climate and Atmospheric Science)
Abstract The impact of climate change on tropical cyclones (TCs) remains a critical concern, but understanding is limited by short instrumental records and low-resolution prehistoric data. Here, we present the first daily-resolution proxy data for investigating prehistoric TC activity, using a 12-year growth rate record of a fossil Tridacna shell (circa 3 ka BP) from the northern South China Sea (NSCS). By analyzing temporal patterns in the proxy data, we derived monthly TC frequency estimates. While modern TC frequency in the NSCS peaks in autumn (September–October), our results showed that TCs at 3 ka BP occurred more frequently in summer (June–July–August), with approximately 15% higher frequency than present. Combined with paleoclimate records, we suggested that this seasonal shift and increased frequency were likely linked to the relatively northward migration of the Intertropical Convergence Zone, which provided favourable conditions for TC formation and development. Our findings imply that future warming would contribute to earlier TC seasons and increased TC frequency in the NSCS.